Complement gene variants determine the risk of immunoglobulin-associated MPGN and C3 glomerulopathy and predict long-term renal outcome. (March 2016) - Iatropoulos, Paraskevas; Noris, Marina; Mele, Caterina; Piras, Rossella; Valoti, Elisabetta; Bresin, Elena; Curreri, Manuela; Mondo, Elena; Zito, Anna; Gamba, Sara; Bettoni, Serena; Murer, Luisa; et al.
Highlights: Rare pathogenic variants and a common SNP of THBD predispose to C3 glomerulopathy. Mutations increase the risk of Ig-MPGN/C3 G only when combined with common SNPs. Patients with complement gene mutations or C3NeF have a lower risk of ESRD. Abstract: Background: Membranoproliferative glomerulonephritis (MPGN) is an uncommon cause of chronic nephropathy recently reclassified into immunoglobulin-associated MPGN (Ig-MPGN) and C3 glomerulopathy (C3G). In this study we aimed: (1) to evaluate the complement genetic and biochemical profile in patients with Ig-MPGN/C3G; (2) to investigate whether genetic variants and different patterns of complement activation (i.e., fluid versus solid phase) correlate with disease manifestations and outcomes. Methods: In 140 patients with idiopathic Ig-MPGN or C3G we performed complement biochemical and genetic screening and correlated genetic, biochemical and histology data with clinical features. Results: Mutations in genes encoding alternative pathway complement proteins were found in both Ig-MPGN and C3G, and mutations in the two components of the C3 convertase are the most prevalent. We also report a mutation in THBD encoding thrombomodulin in a C3G patient. The presence of mutations alone does not significantly increase the risk of Ig-MPGN or C3G, but it does so when combined with common susceptibility variants ( CD46 c.-366A in Ig-MPGN; CFH V62 and THBD A473 in C3G). Finally, patients without complement gene mutations or C3NeFs – autoantibodies that stabilize the alternative pathway C3 convertase – have a higher risk of progressing to end-stage renal disease than patients with identified mutations and/or C3NeFs, suggesting the existence of different pathogenetic mechanisms that lead to renal disease. Conclusions: We provide new insights into the pathogenesis of Ig-MPGN/C3G that underscore the complex nature of these diseases and suggest that the current C3G classification may miss many cases associated with abnormalities of the complement alternative pathway.